Adjunctive effects of intermittent fasting and exercise with glibenclamide on diabetic nephropathy in rats: a potential role of the polyol pathway - Samir, Shereen M.; Hassan, Hend M.; Elmowafy, Rasha; Ebrahim, Neven A.; Albadawi, Emad A.; Albadrani, Muayad; Owaydhah, Wejdan Hussain; Elhadidy, Mona G. (Frontiers in Physiology, 2025)
BackgroundDiabetic nephropathy (DN) is a major complication of type 2 diabetes, often driven by hyperglycemia-induced activation of the polyol pathway. Exercise and intermittent fasting (IF) are non-pharmacological strategies known to improve glucose homeostasis, yet their renal protective roles remain underexplored.AimTo explore how exercise and IF with glibenclamide therapy can have a therapeutic potential in diabetic nephropathy as adjuncts or alternatives to conventional pharmacological treatment by focusing on the polyol pathway as a mechanistic target.MethodsType 2 diabetes was induced in rats using an 8-week high-fat diet followed by a single low dose of streptozotocin (STZ). Animals were treated for 4 weeks with glibenclamide (1 mg/kg/day), exercise, IF, or combined triple therapy. Biochemical, molecular, and histopathological analyses were performed to evaluate renal function, oxidative stress, inflammatory mediators, polyol pathway activity, apoptotic markers, and tissue architecture.ResultsUntreated diabetic rats developed hyperglycemia, renal impairment, oxidative stress, and inflammation with marked polyol pathway activation. Triple therapy significantly improved glycemic control, restored antioxidant defenses, reduced pro-inflammatory and apoptotic markers, downregulated transforming growth factor-β (TGF-β) expression, and preserved renal histology.ConclusionThe combination of glibenclamide, exercise, and IF provides synergistic protection against diabetes-induced nephropathy, primarily through modulation of the polyol pathway, antioxidant enhancement, and suppression of inflammation and fibrosis.